Choice Architecture Improves Pension Selection - Lopez-Tapia, M; Laroze-Prehn, D (Routledge, 2021)
Consumers in Chile of private and semi-private pension systems are not selecting the pension providers that give them the largest Net Present Value. Regulators present retirees with a comparison report of pension plan offerings ranked by the amount offered and the risk classification of the provider. A field experiment implemented in Chile explores alternative presentations of provider performance. We treat respondents by modifying the status quo information ‘package’ (that exactly replicate what is currently provided by the regulator). Two design choices clearly enhanced consumer welfare in this experiment: Reducing the amount of information improved choice–specifically eliminating the risk profiles of providers leads to better decisions by our respondents. Second, adopting a loss frame also resulted in respondents selecting providers that generated higher returns. These gains from modifying information presentation were considerably higher for those with lower levels of financial literacy. This study is conducted in association with the Superintendencia de Pensiones (SP) and the Comisión para el Mercado Financiero (CMF), two of the public offices that oversee the pensions market in Chile. © 2021 Informa UK Limited, trading as Taylor & Francis Group.